Neonatal hemochromatosis. The regulation of transferrin-receptor and ferritin synthesis by iron in cultured fibroblastic-line cells. - Knisely, A. S. (1989)
The authors have investigated the hypothesis that neonatal hemochromatosis (NH), a generally fatal disease of infancy, is due to abnormalities in cellular response to ambient levels of iron. The clinical and necropsy findings in two infants with NH, the results of evaluations for iron-storage disease in their first-degree relatives, and the results of the authors' studies of ferritin and transferrin-receptor (TfR) synthesis in NH and normal fibroblasts are presented. No differences between cultured skin fibroblasts from a normal infant and similar cells from the two infants with NH were seen with respect to TfR and ferritin synthesis rates or their modulation by iron. NH and adult idiopathic hemochromatosis (AH) share a pattern of siderosis in which epithelial and mesenchymal elements contain large quantities of stainable iron, while reticuloendothelial elements contain almost none. Although no familial correlation between NH and AH has been established, and none appeared to exist in these two families, the authors' results parallel those of previous studies of various cell types from persons with AH. The abnormalities in cellular iron handling, undefined at present, that are associated with the phenotype common to NH and AH do not appear primarily to involve the regulation by iron of rates of TfR and ferritin synthesis.